MIGRATION IN BRAZILIAN AFRO-DESCENDANTS COMMUNITIES: A NEW APPROACH TO ILLUSTRATE THE MEANING OF CONTEMPORARY QUILOMBO - Guimarães Paiva, Sabrina; Carvalho Gontijo, Carolina; Carvalho Gontijo, Raquel; Madrigal, Lorena; Klautau-Guimarães, Maria de Nazaré; de Oliveira, Silviene Fabiana (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
African-descendant populations in Latin America are heterogeneous in their history, culture, and genetic ancestry. In Brazil, these communities are known as quilombos. They were at first established as places of resistance to slavery in rural areas. However, others were formed as a result of a recent immigration. This has given rise to the discussion of how well all such groups fit the contemporary meaning of quilombo. We draw on evidence from field research in Central Brazil to illustrate two examples of quilombos, a quilombo with families in the community for at least three generations, and others that are related to migration of Black communities. We call for an expansive meaning of quilombo that accommodates the historical diversity of these communities.